2009
DOI: 10.1016/s0929-6646(10)60009-5
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Reference Intervals for Several Biochemical Analytes in School Children in Central Taiwan

Abstract: Our study provides new pediatric reference intervals (2.5th-97.5th percentiles) of 60-99 mg/dL for serum glucose concentrations, 8-38 IU/L for ALT, 0.4-1.1 mg/L for Cr, 8.7-18.0 mg/L for BUN, and 10-34 for B/C ratio. The B/C ratio in children was higher than those of adults, possibly due to that children had a higher intake of protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 19 publications
2
10
1
Order By: Relevance
“…For example, the study by Gomez et al found patterns in creatinine, total bilirubin, and LDH con-centrations that were similar to those of our study when they were plotted over time and that reflected the underlying physiological changes that occur throughout childhood (35 ). Similarly, the trends in our data for alanine aminotransferase and creatinine showed similarities to the data presented by Lai et al, who studied a population that included 5000 healthy participants from 3 years of age to adult (34 ). The CALIPER reference intervals obtained for creatinine (enzymatic) in the present study were also closely similar to the ageadjusted reference intervals reported by Ceriotti et al (26 ), likely owing to the use of isotope-dilution mass spectroscopy-standardized methods in both studies.…”
Section: Discussionsupporting
confidence: 88%
“…For example, the study by Gomez et al found patterns in creatinine, total bilirubin, and LDH con-centrations that were similar to those of our study when they were plotted over time and that reflected the underlying physiological changes that occur throughout childhood (35 ). Similarly, the trends in our data for alanine aminotransferase and creatinine showed similarities to the data presented by Lai et al, who studied a population that included 5000 healthy participants from 3 years of age to adult (34 ). The CALIPER reference intervals obtained for creatinine (enzymatic) in the present study were also closely similar to the ageadjusted reference intervals reported by Ceriotti et al (26 ), likely owing to the use of isotope-dilution mass spectroscopy-standardized methods in both studies.…”
Section: Discussionsupporting
confidence: 88%
“…This finding is consistent with some previous studies in Iranian children and adolescents (5, 14, 17, 26). In a study in Taiwan, the 2.5th-97.5th percentiles of ALT in children are reported 8-38 IU/L with significantly higher levels in boys than in girls (13). Likewise, in Australian adolescents both enzyme values were higher in boys than in girls (12).…”
Section: Discussionmentioning
confidence: 99%
“…Several papers containing age-specific reference values of serum urea have been published [62,63]. Unlike creatinine, serum urea levels are not clearly age-related but rather reflect fluid and protein intake and metabolism.…”
Section: Reference Values In Childrenmentioning
confidence: 99%